Numerical Modeling of Cracked Arch Dams. Effect of Open Joints during the Construction Phase - André Conde; Eduardo Salete; Miguel Á. Toledo (Infrastructures, 2024)
Running a numerical model for a cracked arch dam that takes into account all the particularities of the materials and dam with a high level of detail has a great computational cost involved. For this reason, it is usual to simplify such a model in search of a simpler solution while preserving the characteristic of being representative, with all the particularities that the model of an arch dam has. A common simplification lies in not considering open transverse joints in the construction phase of a cracked dam. An aim of this study is to propose a methodology that combines open joints and cracking, something on which, to the authors’ knowledge, no studies have been published. An additional goal is a study of the need and adequacy of different approaches on performance (computational time) and its consequences for model accuracy. For this purpose, an accurate methodology for a stationary finite element method numerical simulation of deformations in cracked arch dams is presented. Using a tetrahedron mesh of a real dam, different simplifications commonly used in numerical models are compared. It is concluded that some of the standard simplifications produce a significant effect on the computation time and accuracy of the results.